The Effect of Tera Gymnastics to Decrease Blood Pressure in Elderly Hypertension in UPT Babakan Sari Community Health Center - Irawan, Erna; Maidartati, Maidartati; Iklima, Nurul; Tania, Mery; Yulia, Yulia (Universitas Pendidikan Indonesia, 2024)
Introduction: Hypertension is one of the leading causes of premature death worldwide. Hypertension is defined as a persistent increase in blood pressure, where systolic pressure exceeds 140 mmHg and diastolic pressure exceeds 90 mmHg. One of the therapies that can be used to lower blood pressure is Tera gymnastics, which is specifically designed for the elderly and individuals with hypertension. This therapy involves regular, structured, and planned movements that are slower and more harmonious compared to other types of gymnastics, reducing the risk of injury and promoting overall fitness in the elderly. The purpose of this study was to examine the effect of Tera gymnastics on reducing blood pressure in elderly individuals with hypertension. Methods: This study used a quasi-experimental design with a one-group pretest-posttest approach. The sampling technique employed was purposive sampling, involving 17 respondents from the Babakan Sari Community Health Center, RW 09. Instruments used in this study included a digital sphygmomanometer, a stethoscope, and observation sheets. Results: The results of the t-test analysis showed a significant effect of Tera gymnastics on blood pressure reduction, with a p-value of 0.000 ( 0.05) for both systolic and diastolic pressures. The average blood pressure before the intervention was 140/179 mmHg, while the average blood pressure after the intervention was 132/157 mmHg. The movements in Tera gymnastics improve blood circulation, making it a suitable alternative therapy for individuals with hypertension. Conclusion: Tera gymnastics has a significant influence on reducing blood pressure in elderly individuals with hypertension at UPT Babakan Sari RW 09, Bandung City. It is suggested that community health cadres continue implementing Tera gymnastics as an alternative treatment for hypertension. Additionally, it is recommended to perform Tera gymnastics three times a week to maintain blood pressure stability in elderly individuals with hypertension.